PENGARUH KONDISI TATANAN FISIK TERHADAP KENYAMANAN PENGUNJUNG PADA TAMAN VATULEMO DI KOTA PALU - Afniyanti Bandaso; Retno Widjajanti (Diponegoro University, 2019)
The basic understanding in creating public space is trying to always meet the needs of its users. The importance of the city park as a public space, the Palu City Government is renovating Vatulemo Park as a public space with the provision of facilities and infrastructure. The trend of developing Vatulemo Park has resulted in changes in space use. Various activities that can be accommodated in Vatulemo Park on the one hand show the development of Vatulemo Park as a public space, on the other hand it is feared that it can cause conflict between activities and reduce the quality of comfort for visitors to Vatulemo Park. This study aims to determine the effect of physical order conditions on comfort at Vatulemo Park in Palu City. The method of analysis is done by quantitative descriptive. Data is obtained by conducting surveys and questionnaires. From the results of the analysis of the influence of physical order conditions on the convenience of visitors, it was found that the influence of physical conditions was the most significant, namely the physical order of the pedestrian path with a significant value of 0.625. From the results of the study it can be concluded that the condition of the physical order of visitors' comfort is influenced by the arrangement of parks that can support visitor activities in Vatulemo Park, such as the physical order of the pedestrian route, the physical parking structure, the physical order of signification elements, the physical order of supporting activities and the physical order of the circulation path.